Personnel Cooperation Between University and Industrial Partners in the Context of Youth Career Development - S. A. Miroshnikov; S. V. Notova; Yu. N. Nikulina (Высшее образование в России)
The article has a research, practice-oriented nature and analyzes the problems of professional development and building a career trajectory of graduates through the prism of the personnel partnership of university and the business community. The purpose of the article is to explore the personnel cooperation between university and industrial partners in the context of professional development tracks and, in the light of this, develop a cyclogram of youth career development.The article presents the results of the study of factors influencing the formation of a career trajectory from the position of students of Orenburg State University (2022). The practice of implementing the formats of personnel partnership of the university and employers of Orenburg State University, including various activities within the framework of building the trajectory of professional and career development of a future specialist, is analyzed.The authors propose recommendations for the development of a cyclogram of students’ career development, improvement of the efficiency of interaction between the university and personnel partners by creating a student association of professional development focused on enhancement of career guidance activities at university, identifying creative, scientific, and entrepreneurial potential of students, developing skills necessary to increase competitiveness in the labor market, assistance in career planning and building of university students and graduates.